THE HUMAN RIGHTS IN INDONESIA AS SEEN THROUGH VARIOUS ASPECTS OF LEGAL AND CUSTOM LIFE - Dadang Sumarna; Yenny Febrianty; Marjan Miharja; Yahman Yahman; Christopher Panal Lumban Gaol (UNISSULA, 2023)
The purpose of this research is to analyze Human Rights in Indonesia from a Legal Perspective and a Customary Life Perspective. Based on Indonesian law and the way of life in each region, regional regulations are established to protect inhabitants' human rights. This research was carried out using normative methods with research through a literature study. As a guarantee of the notion of equality among all humans, HAM, or human rights, is a fundamental value that must be safeguarded and maintained. It is not just in Indonesia but anywhere else in the world. Right now, there is an imbalance between the respect for human rights and how those rights are put into practice. In spite of these circumstances, Indonesian conversation and debate are nonetheless highly fascinating. With regard to human rights, in particular. In order to examine human rights in relation to various legal and customary aspects of life in Indonesia, this research was conducted utilizing the literature review technique. The findings of this research describe the state of human rights in light of Indonesia's legislative and cultural traditions. The issue of indigenous peoples has indeed become one of the strongest issues in international development. Indigenous peoples are a community group that must receive attention in mitigation and adaptation efforts.